Effect of sowing technique on growth of undersown crop and yield of spring barley - Känkänen, Hannu; Mikkola, Hannu Juhani; Eriksson, Christian (Blackwell, 2001)
Undersowing a main crop enables establishment of a catch crop in areas characterized by a short post-harvest period before the onset of winter. Techniques with lower costs than conventional undersowing by separate drilling are often regarded as unreliable. Undersowing by drilling after sowing spring barley (Hordeum vulgare L.) was compared with broadcast sowing simultaneously with drilling barley. Various implements were coupled behind the combined drill in cases where seed was broadcast: a press-wheel attachment, a long-tined harrow and a cage roller. A fourth treatment did not include an implement coupled behind the drill. The undersown crop was sown as a seed mixture of 3 kg ha-1 red clover (Trifolium pratense L.) and 6 kg ha-1 meadow fescue (Festuca pratensis Hudson). The numbers of plants and weeds and the plant height were measured five times during the growing season. Above-ground biomass of the undersown species was determined at barley harvest and in late autumn. Grain yield of spring barley was recorded. Drilling resulted in the highest yield of undersown crop when an early summer drought occurred, but broadcasting in combination with use of seed covering equipment led to the least variation in biomass production over the 4 years the experiment was conducted. The relative proportion of meadow fescue in the crop was low in three years, and lower when broadcast than when drilled. Barley grain yield was highest when the seed was broadcast and seed covering equipment was used. Use of a cage roller creased weed biomass, but press-wheels and a long-tined harrow did not. Separate rolling after undersowing increased undersown crop yield in one year, but decreased grain yield in some cases.
Keywords: Ka; aluskasvit; ohra; biomassa; Festuca pratensis; Trifolium pratense; kylvötekniikka; rikkakasvit; biomass; Festuca pratensis; sowing technique; spring barley; Trifolium pratense; undersowing; weeds